Pengaruh Teori-teori Belajar dalam Pendidikan Agama Kristen - Dethan, Vivi; Sutrisno, Gideon (Institut Agama Kristen Negeri Kupang, 2025)
This study aims to examine the application of behaviorist, humanistic, cognitive, and constructivist learning theories in the implementation of Christian Religious Education (PAK), particularly in the context of children's learning. As an integral part of the Christian education system, PAK requires relevant and contextual approaches to effectively shape character, spirituality, and a deep understanding of faith in learners. This research employs a qualitative descriptive approach through a literature review method. Data were collected from various scholarly sources, including books, journal articles, and previous research findings. The results show that each learning theory offers a unique and complementary contribution: behaviorist theory emphasizes behavior formation through stimulus and reinforcement; humanistic theory focuses on the holistic development of personal potential; cognitive theory highlights thinking processes and cognitive development; while constructivist theory encourages active learning through experience and personal reflection. When applied appropriately and contextually, these four theories can make PAK a holistic, transformative learning process that is deeply rooted in Christian values.